Venous thromboembolic events in patients with COVID-19: a systematic review and meta-analysis. (17th November 2020) - Wu, Ting; Zuo, Zhihong; Yang, Deyi; Luo, Xuan; Jiang, Liping; Xia, Zanxian; Xiao, Xiaojuan; Liu, Jing; Ye, Mao; Deng, Meichun
Abstract: Background: High incidence of venous thromboembolic complications in coronavirus disease 2019 (COVID-19) patients was noted recently. Objective: This study aimed to explore the factors associated with prevalence of venous thromboembolism (VTE) in COVID-19 patients. Methods: A literature search was conducted in several online databases. Fixed effects meta-analysis was performed for the factors associated with prevalence of VTE in COVID-19 patients. Results: A total of 39 studies were analysed in this analysis. The incidence of pulmonary embolism and VTE in severe COVID-19 patients were 17% (95% CI, 13–21%) and 42% (95% CI, 25–60%), respectively. VTE were more common among individuals with COVID-19 of advance age. Male COVID-19 patients are more likely to experience VTE. Higher levels of white blood cell (WBC; WMD = 1.34 × 10 9 /L; 95% CI, 0.84–1.84 × 10 9 /L), D-dimer (WMD = 4.21 μg/ml; 95% CI, 3.77–4.66 μg/ml), activated partial thromboplastin time (APTT; WMD = 2.03 s; 95% CI, 0.83–3.24 s), fibrinogen (WMD = 0.49 μg/ml; 95% CI, 0.18–0.79 g/L) and C-reactive protein (CRP; WMD = 21.89 mg/L; 95% CI, 11.44–32.34 mg/L) were commonly noted in COVID-19 patients with VTE. Patients with lower level of lymphocyte (WMD = −0.15 × 10 9 /L; 95% CI, −0.23-−0.07 × 10 9 /L) was at high risk of developing VTE. The incidence of severe condition (OR = 2.66; 95% CI, 1.95–3.62) was more likely to occur among COVID-19 patients who developed VTE. Conclusion: VTE is a common complication in severe COVID-19 patients and thromboembolic events are also associated with adverse outcomes.